POTENSI WISATA ALAM DI KOTA PAGAR ALAM, PROVINSI SUMATERA SELATAN BERDASARKAN PENAWARAN, PERMINTAAN DAN DAYA DUKUNG - yogie zulni pratama; Rinekso Soekmadi; Afra DN Makalew (Tengkawang : Jurnal Ilmu Kehutanan, 2021)
Pagar Alam City belongs to the administrative region of South Sumatera Province and has a variety of natural tourism to be developed. This research focuses on determining natural tourism potentials based on supply, demand and carry capacity in Pagar Alam City. The assessment used the analysis of potential objects and natural attractions using the guidelines for regional analysis of operations-objects and natural attractions (ADO- ODTWA) from Directorate General of Forest Protection and Nature Conservation (2003) and carrying capacity’s analysis using the formula Douglass (1982). The results showed that Pagar Alam city has 7 natural tourism potential dan 29 natural tourism enough potential with the highest potency value index of the Dempo Mountain Tea Plantation Area 87.89% and the lowest 33.51% is Blange Water Fall. The number of tourists according to carrying capacity for each tourism activities are recreational activities 1.041.336 people/year and camping activities 555.685 people/year.Keywords: demand, carrying capacity, natural tourism, supply, tourist.AbstrakKota Pagar Alam termasuk dalam wilayah Provinsi Sumatera Selatan dan memiliki berbagai wisata alam untuk dikembangkan. Fokus penelitian adalah kajian potensi wisata alam di Kota Pagar Alam, Sumatera Selatan berdasarkan penawaran, permintaan dan daya dukung di Kota Pagar Alam. Penilaian yang digunakan adalah analisis potensi objek dan daya tarik wisata alam menggunakan pedoman analisis daerah operasi-objek dan daya tarik wisata alam (ADO-ODTWA) Direktorat Jendral Perlindungan Hutan dan Konservasi Alam (2003) dan analisis daya dukung menggunakan formula Douglass (1982). Hasil penelitian menunjukkan bahwa Kota Pagar Alam memiliki 7 wisata alam yang berpotensi dan 29 wisata alam cukup berpotensi untuk dikembangkan dengan indeks nilai potensi tertinggi yaitu Kawasan Perkebunan Teh Gunung Dempo dengan persentase 87.89% dan terendah 33.51% yaitu Cughup Blange. Jumlah wisatawan sesuai dengan daya dukung untuk masing-masing kegiatan wisata yaitu kegiatan rekreasi adalah 1.041.336 orang/tahun dan kegiatan wisata 555.685 orang/tahun.Kata kunci: daya dukung, penawaran, permintaan, wisawatan, wisata alam